(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Nutrient evaluation and phytochemical screening of four selected wild plants seed from Kainji Lake National Park Range were carried out. The selected plants include Detarium microcarpum, Daniela olivera, Vitallaria paradoxa and Entanda africana. The various plant seeds were analysed for their proximate composition and the mean range values of moisture (5.09±0.24 to 6.73±1.11 g/100 g), ash (2.65±0.27 to 9.93±0.65 g/100 g), Crude fibres (1.24±0.10 to 6.75±0.37 g/100 g), crude protein (13.26±0.66 g/100 g), crude fat (8.72±0.42 to 16.00±0.68 g/100 g) and the calculated NFE range (54.53±0.27 g/100 g) were reported. Result revealed that all the plant seeds used were low in moisture contents an attributes for good storage and packaging for animal feed ratios. The qualitative analysis showed the presence of saponins, flavonoids, alkaloids, tannins, cardiac glycosides. Triterpenoids, quinine, sterols and traces of carbohydrate in Vitellaria paradoxa only. While phenol was not detected in all the plant seeds examined. The presence of saponins in all the plant seeds studied it is an indication that the seeds could be described as a potential source of natural antioxidants. This study therefore concluded that the phytochemical constituents revealed in some of the seed samples can be correlated with its medicinal properties used by traditional herbal healers around the study area. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 91-98